Estimasi Biaya Pengembangan Perangkat Lunak Menggunakan Metode Fuzzy Use Case Point (Studi Kasus: Dinas Komunikasi dan Informatika Kota Batu) - Krisdian Widya Ekatama; Widhi Hayuhardhika Nugraha Putra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Department of Communication and Information (DISKOMINFO) of Batu does not yet have a specific method for estimating the development of information systems or applications, the thing that is used as a reference is the standard operating procedure that contains the application development flow with 3 months of time being carried out with assistance only. This raises several problems such as the lack of time from 3 months to develop the application. This research was conducted to analyze the comparison of estimation using the Fuzzy Use Case Point method with actual conditions. There are 6 applications that become case studies in this study. Data collection was carried out by observation, interviews, and the use of assessment sheets with respondent Head of Application Development Unit of DISKOMINFO Batu. Estimation using the Fuzzy Use Case Point method produces a smaller estimate compared to the actual condition with the average value of percent error is 36.62% for the duration of work and 69.99% for the total cost. Scheduling for each application development is represented in the Work Breakdown Structure (WBS) and then arranged into a Gantt Chart, based on predetermined activities.The results of this study can be taken into consideration for DISKOMINFO of Batu to carry out an analysis of resource estimates that are useful for improving standard operating procedure or also when collaborating with vendor in terms of agreement on estimating resource for application development.